Problems of Teachers in The Taeching of Imla for Students of the Ninth Semester in The Islamic Integrated Secondary School “Imam Syafi’i” East Java - Putri Nur Jannah (Prodi Pendidikan Agama Islam, Fakultas Tarbiyah, Universitas Darussalam Gontor, 2019)
Integrated Islamic Junior High School (SMPIT) Imam Syafi'i is a school that combines the learning of common lessons with islamic lessons in a balanced way. Standing under the auspices of the Ministry of Education and Culture of the Republic of Indonesia. One lesson of Dirosah Lughowiyah taught in this school is imla' lesson.Imla’ has an important role to instill in student’s mastery of Arabic language because imla' is the first step in Arabic language learning in terms of writing skills, and has a close relationship with other skills of speaking and reading skills. Imla’ lesson for 9th graders is a new lesson to be held in this academic year and the advantages of this school compared to other Integrated Islamic Junior High School in this area. The curriculum for this lesson was not provided by the Indonesian National Education Department. Type of research used by writer is descriptive qualitative research. And to achieve the above goals the author uses interviews, observation and documentation, then use Miles and Huberman method to draw conclusions from the data obtained. With Descriptive method, then the author describes the data. This article concludes that the teaching of imla’ in this school has not run well and the teaching’s action is not yet organized. And found some problems from the teacher side during the ongoing teaching activities that can cause teacher failure in teaching this lesson.